The impact of risks on small and medium enterprises in the region of Sebha- Libya 2010- 2019 - Elgafari, Mohammed Elnagi; Algohaimi, Ehmaid Abu Khanger Mohammed (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the reality of the small and medium enterprises in Libya and the role of financial risks management in the success of these projects. The study followed the historical descriptive method and the quantitative methodology. The data were collected by means of a questionnaire, distributed to a simple random sample of small and medium enterprises, and analyzed through the SPSS program. The study found that, the lack of liquidity and the risk of repayment of loans come at the forefront of the financial risks affecting small and medium enterprises in the region of Sabha in Libya. The most important recommendations of the study: the need to develop the strategy of small and medium enterprises, after a careful and realistic analysis of its environment. Develop a realistic strategy for projects, taking into account the risks faced by these enterprises.